Optometric Care of the Patient with Diabetes 2008: A Core Document of the Canadian Association of Optometrists - Koltun, Len (Canadian Journal of Optometry, 2008)
The objective of this document is to provide the reader with an overview of the epidemic of diabetes currently facing Canada and the morbidity and mortality associated with this growing healthcare burden. Specifically, an evidence based, patient centered, cost effective role of the optometrist in the eye care of Canadians with diabetes will be presented.